The Use of the Nitroblue Tetrazolium Test in Blood Granulocytes for Discriminating Bacterial and Non-Bacterial Neutrophilic Dermatitis - Marina García; Icíar Martínez-Flórez; Laia Solano-Gallego; Nuria García; Laura Ordeix (Veterinary Sciences)
This study aimed to evaluate differences in the production of reactive oxygen species (ROS) by peripheral blood neutrophils in healthy dogs, dogs with superficial pyoderma, and dogs with sterile neutrophilic dermatitis using the nitroblue tetrazolium (NBT) reduction test. Additionally, the study assessed the potential of the NBT reduction test as a diagnostic tool to differentiate between these clinical conditions. A total of 28 dogs were divided into three groups: healthy (n = 10), superficial pyoderma (n = 10), and sterile neutrophilic dermatitis (n = 8). The results showed significantly higher neutrophil activation in dogs with sterile neutrophilic dermatitis (19 ± 10%) compared with healthy dogs (7.3 ± 5%) (p < 0.01) and dogs with superficial pyoderma (10 ± 2.8%) (p < 0.05). Dogs with sterile neutrophilic dermatitis and a high positive result for Leishmania spp. antibodies (n = 3) exhibited even higher NBT reduction rates (30 ± 4.6%) compared with seronegative dogs with sterile neutrophilic dermatitis (n = 5) (13 ± 5.3%) (p < 0.05). These findings suggest that the NBT reduction test could be useful for detecting systemic neutrophil activation in sterile neutrophilic dermatitis, especially when associated with Leishmania infection. However, no significant differences were observed between healthy dogs and those with superficial pyoderma, indicating that the test may not be effective in detecting systemic neutrophil activation in superficial bacterial infections.